Analisis Kinerja Keuangan PT Medco Energi Internasional Tbk Periode 2020–2024 - Ni Ketut Suksestriyani; Nengah Sukendri (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This study was conducted to evaluate the financial performance of PT Medco Energi Internasional Tbk for the 2020–2024 period through the application of financial ratio analysis methods. This study uses a quantitative descriptive approach utilizing secondary data in the form of annual financial reports published by the Indonesia Stock Exchange. Analysis was conducted on liquidity, solvency, profitability, and activity ratios to assess the company's ability to meet short-term and long-term obligations, generate profits, and manage assets efficiently. The results show that the company's liquidity ratios are generally above the minimum standard, although they fluctuate. Solvency ratios indicate a relatively high level of leverage, especially at the beginning of the pandemic period, but tend to improve in subsequent years. In terms of profitability, the company has successfully experienced a significant recovery, shifting from a loss in 2020 to a profit that has consistently increased until 2024. Furthermore, activity ratios indicate an increase in the efficiency of asset utilization to support sales growth. Overall, the financial performance of PT Medco Energi Internasional Tbk shows a trend of recovery and strengthening post-COVID-19 pandemic.